Acute coronary insufficiency. An urgent surgical condition. Issue 10 (October 1975) - Lawson, R M; Chapman, R; Wood, J; Starr, A
Abstract : In 41 of 220 consecutive patients who had a coronary artery bypass operation between July 1973 and March 1974 the operation was for acute coronary insufficiency (recurrent chest pain with transient electrocardiographic changes persisting after admission to hospital). Their mean age was 54 (range 33-70 years). Eleven patients had had angina before, 14 had had at least one myocardial infarction, and 16 presented de novo. Eight of the latter 16 patients required only a single graft, usually to the left anterior descending artery, a significantly greater number than the two of the other 25 patients (P less than 0.01). Fourteen of these 16 patients had normal ventricular contraction, a significantly higher proportion than the 13 of the remaining 25 (p less than 0.05). No collaterals were seen in any of the 10 with single-vessel disease, which was significantly fewer than five out of 18 with double- and nine out of 13 with triple-vessel disease (P less than 0.005). Patients with rapidly developing obstruction, especially in the proximal left anterior descending artery, may not have time to develop collaterals, present acutely with good ventricular function, and may be particularly at risk. There was no operative mortality. The patients had a perioperative myocardial infarction, and there was one late death. At follow-up averaging 9-7 months (range 5-14 months) 32 (80%) patients were angina-free, no myocardial infarctions had occurred, and 85% were fully employed. Urgent coronary artery bypass grafting is a safe and effective treatment for acute coronary insufficiency.